83.8k views
1 vote
What is the solution to the following equation?

3(7x - 12) + 26 =3x -10

A) 0
B) 1
C) 5
D) 8

2 Answers

3 votes
1) Distribute the 3 to the 7x and the 12 using the distributive property. Then simplify:
3(7x - 12) + 26 = 3x - 10
21x - 36 + 26 = 3x - 10
21x - 10 = 3x - 10

2) Get all the variables to one side of the equation and everything else to the other side:
21x - 10 = 3x - 10
18x - 10 = -10
18x = 0
x = 0

-----

Answer: x = 0

User LuVa
by
5.7k points
4 votes
Hey there!:

3 ( 7 x - 12 ) + 26 = 3x - 10

3 * 7x - 3 * 12 + 26 = 3x - 10

21 x - 36 + 26 = 3x - 10

21x - 3x = - 10 + 36 - 26

18 x = 0

x = 0 / 18

x = 0

Answer A
User Skuta
by
5.1k points